Blending hydrogen in existing natural gas pipelines: Integrity consequences from a fitness for service perspective - Kappes, Mariano A.; Perez, Teresa E. (Journal of Pipeline Science and Engineering, 2023)
Blending hydrogen in existing natural gas pipelines compromises steel integrity because it increases fatigue crack growth, promotes subcritical cracking and decreases fracture toughness. In this regard, several laboratories reported that the fracture toughness measured in a hydrogen containing gaseous atmosphere, KIH, can be 50% or less than KIC, the fracture toughness measured in air. From a pipeline integrity perspective, fracture mechanics predicts that injecting hydrogen in a natural gas pipeline decreases the failure pressure and the size of the critical flaw at a given pressure level. For a pipeline with a given flaw size, as shown in this work, the effect of Hydrogen Embrittlement (HE) in the predicted failure pressure is largest when a failure occurs by a brittle fracture. The HE effect on failure pressure diminishes with a decreasing crack size or increasing fracture toughness. The safety margin after a successful hydrostatic test is reduced and therefore the time between hydrotests should be decreased. In this work, all those effects were quantified using a crack assessment methodology (level 2, API 579-ASME FFS) considering literature values for KIH and KIC reported for an API 5L X52 pipeline steel. To characterize different scenarios, various crack sizes were assumed, including a small crack with a size close to the detection limit of current in-line inspection techniques and a larger crack that represents the largest crack size that could survive a hydrotest to 100% of the steel Specified Minimum Yield Strength (SMYS). The implications of a smaller failure pressure and smaller critical crack size on pipeline integrity are discussed in this paper.